2003
DOI: 10.2337/diabetes.52.8.2066
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Inhibitory Amino Acid Transporter Is Present in Glucagon-Containing Secretory Granules in αTC6 Cells, Mouse Clonal α-Cells, and α-Cells of Islets of Langerhans

Abstract: Islets of Langerhans contain ␥-aminobutyrate (GABA) and may use it as an intercellular transmitter. In ␤-cells, GABA is stored in synaptic-like microvesicles and secreted through Ca 2؉ -dependent exocytosis. Vesicular inhibitory amino acid transporter (VIAAT), which is responsible for the storage of GABA and glycine in neuronal synaptic vesicles, is believed to be responsible for the storage and secretion of GABA in ␤-cells. . Islets of Langerhans contain GABA, the enzymes that catalyze its biosynthesis (GAD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
3
17
1
Order By: Relevance
“…Results published subsequently have been conflicting (Hayashi et al 2003a, Gammelsaeter et al 2004. The immunostaining results shown herein provide further evidence of cell expression of VIAAT.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Results published subsequently have been conflicting (Hayashi et al 2003a, Gammelsaeter et al 2004. The immunostaining results shown herein provide further evidence of cell expression of VIAAT.…”
Section: Discussionsupporting
confidence: 51%
“…Lower levels of VIAAT were also detected in the rat islet cells, which contain GAD65 (Chessler et al 2002). Hayashi et al (2003a) subsequently confirmed the presence of VIAAT in the rat islet mantle, detecting none in the islet cells. Unexpectedly, VIAAT was found to localize to the glucagon-containing secretory granules rather than to the synaptic-like microvesicles also present in islet cells.…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…Similar conclusions were obtained in mouse islets and clonal aTC1-9 cells (Xu et al 2006, Bailey et al 2007). The neurotransmitter L-glutamate also accumulates in the a-cell secretory granules because of vesicular glutamate transporters 1 and 2 found in these cells (Hayashi et al 2003a). In low-glucose conditions, L-glutamate is cosecreted with glucagon, triggering GABA release from neighbouring b-cells and, subsequently, inhibiting the a-cell function as previously described (Hayashi et al 2003b).…”
Section: Glp1mentioning
confidence: 86%